Metaphor in psychosis: on the possible convergence of Lacanian theory and neuro-scientific research - Ribolsi, Michele; Feyaerts, Jasper; Vanheule, Stijn (Frontiers in Psychology, 2015)
Starting from the theories of leading psychiatrists, like Kraepelin and de Clérambault, the French psychoanalyst Jacques Lacan (1901-1981) formulated an original theory of psychosis, focusing on the subject and on the structuring role of language. In particular, he postulated that language makes up the experience of subjectivity and that psychosis is marked by the absence of a crucial metaphorization process. Interestingly, in contemporary psychiatry there is growing empirical evidence that schizophrenia is characterized by abnormal interpretation of verbal and nonverbal information, with a great difficulty to put such information in the appropriate context. Neuroscientific contributions have investigated this difficulty suggesting the possibility of interpreting schizophrenia as a semiotic disorder which makes the patients incapable of understanding the figurative meaning of the metaphoric speech, probably due to a dysfunction of certain right hemisphere areas, such as the right temporoparietal junction and the right superior/middle temporal gyrus. In this paper we first review the Lacanian theory of psychosis and neuro-scientific research in the field of symbolization and metaphoric speech. Next, we discuss possible convergences between both approaches, exploring how they might join and inspire one another. Clinical and neurophysiological research implications are discussed.